(3EOGQI Gdbdbs - (3OGjfR, QhHjfs; (3bSe GdJQLeI HOGQ GdaGQhbs; (3bSe GdJQLeI HOGQ GdaGQhbs ((3GdbGgQIs (3OGQ GdaGQhb ddfTQ h GdJhRjYs, 2006)
(3EOGQI Gdbdb aj YTQI LdSGJ(B. (3dbO Je JCdja gPG GdcJGH NUjkUG deSGYOI Cj TNU jQZH aj hVY HQfGeL dEOGQI Gdbdb dGSJNOGeg eY GdeLehYGJ Ch GdCaQGO(B. (3dPG, aEf GdcJGH eajlO dcd ef GdCNUGFjjf GdGLJeGYjjf heQGbHj GdSdhc hGdeYGdLjf Gdegfjjf hehXaj GdQYGjI hGdeSJTGQjf, hcPdc Cj TNU BNQ jJe GddLhA Edjg ddJYGed eY GdCaQGO GdPjf jYGfhf ef eTcdGJ eJYdbI HGdbdbs
(3eJhGaQ efI GdWHYI GdKGfjI dYGe (B2022 (3aj ecJHI eUQ GdYGeI aQY GShGfs
(3eJhGaQ efI GdWHYI GdKGfjI dYGe (B2023 (3aj ecJHI eUQ GdYGeI GdaQY GdQFjSjs
(3GdfU eJQLe Edi GddZI GdYQHjI ef GddZI GdEfLdjRjIs
1 8 9 10 11 12 13 20
Keywords: (3GdVZW GdYUHjs; (3Gdbdbs